Circles and circuits: Chinese Caribbean art - Chang, Alexandra (Chinese American Museum, 2018)
Circles and Circuits: Chinese Caribbean Art examines artistic production in Cuba, Trinidad, Jamaica, and Panama, where large immigrant populations and political, economic, and socio-cultural conditions enabled the development of rich art practices in the Chinese diasporic community. The volume touches on the dynamic interconnections between the Chinese diasporic art communities and intercontinental Caribbean art movements bringing into focus the intimate relationships between the artists and those around them, including those who influenced their work, from peers to mentors and family
"This publication accompanies the exhibition Circles and Circuits : Chinese Caribbean Art presented in two parts : History and Art of the Chinese Caribbean Diaspora at the California African American Museum, September 15, 2017 through February 25, 2018, Contemporary Chinese Caribbean Art at the Chinese American Museum, September 15, 2017 through March 11, 2018"--Page facing title page
"'Circles and Circuits: Chinese Caribbean Art' is part of Pacific Standard Time: LA/LA ... "--Page facing title page
Keywords: Geschichte 1920-2017; Kunst; Chinesen; Trinidad; Karibik; Jamaika; Panama; Kuba; Art, Chinese / Caribbean Area; Art, Chinese; Caribbean Area; 20.42 Chinese art; 20.54 American art; Caribbean region; Ausstellungskatalog -- California Afro-American Museum -- 15.09.2017-25.02.2018 -- Los Angeles, Calif.; Ausstellungskatalog -- Chinese American Museum -- 15.09.2017-11.03.2018 -- Los Angeles, Calif.